Gender, Agriculture and Assets Project (GAAP) - International Food Policy Research Institute (2010)
The website of the Gender, Agriculture, and Assets Project (GAAP) co-led by the International Food Policy Research Institute (IFPRI) and the International Livestock Research Institute (ILRI) provides information about GAAP, project updates, an overview of projects and a gender and assets toolkit.